Cavovarus Foot Surgery Including a Peroneus Longus Transfer: A 2- to 6-Year Follow-up - Anna E. Sprinchorn MD; Andrew D. Beischer MD (Foot & Ankle Orthopaedics, 2021)
Background: The primary aim of this longitudinal study was to describe patient satisfaction and clinical outcome at least 2 years following cavovarus foot surgery, utilizing a peroneus longus to brevis transfer, lateral ligament reconstruction, and corrective osteotomies of the first metatarsal, occasionally with the added calcaneal osteotomy. Methods: Sixteen patients (17 feet) were examined in 2010-2012, 3.5 (range, 2-6.5) years after cavovarus foot surgery performed in 2004-2010 utilizing a peroneus longus to brevis transfer, lateral ligament reconstruction, and osteotomy of the first metatarsal with or without additional calcaneal osteotomy. The mean age at surgery was 45 years. Evaluation at baseline before surgery and at follow-up assessed patient satisfaction, using the American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score. At follow-up, visual analog scale (VAS) score for pain at walking was recorded, and a clinical and radiographic evaluation was included. Results: The mean AOFAS score improved from 57 (SD 11) to 83 (SD 12.5) points, with an average score improvement of 25 score points (95% confidence interval 16-35, P < .0001). Postoperative VAS score for pain at walking was mean 2 (range, 0-6). All feet had a residual cavovarus both clinically and on the radiographs. Conclusion: Patient satisfaction and clinical outcome was shown to improve pre- to postsurgery at intermediate follow-up after peroneus longus to brevis transfer and metatarsal osteotomies with or without additional calcaneal osteotomies as part of a cavovarus foot correction. Level of Evidence: Level IV, case series.